Quality of Life and Impact of Endoscopic Sinus Surgery in Adult Patients With Cystic Fibrosis. Issue 4 (July 2019) - Lazio, Maria S.; Luparello, Paolo; Mannelli, Giuditta; Santoro, Giovanni P.; Bresci, Silvia; Braggion, Cesare; Gallo, Oreste; Maggiore, Giandomenico
Background: Cystic fibrosis (CF) is the most common autosomal recessive disease in Caucasian population. Due to its pathological mechanism, chronic rhino sinusitis (CRS) associated or not with nasal polyposis usually occurs in adults and affects close to one-half of all CF patients. The goal of our work was to evaluate the impact of endoscopic sinus surgery (ESS) in the quality of life (QoL) of the CF patients and demonstrate an improvement of the functional outcomes in the patients undergoing the surgical procedure rather than in the not treated ones. Methodology : We studied 54 adult patients affected by CF. Lund–Kennedy, Lund–Mackay scores, and Sino-Nasal Outcome Test-22 (SNOT-22) were analyzed. Results: Twenty-two (40.7%) of the 54 CF patients underwent ESS. This group presented more likely complaints consistent with CRS. Lund–Kennedy and Lund–Mackay scores appeared higher in the ESS group: 10 (range of 6–12) and 16 (range of 12–20), respectively. SNOT-22 showed median values for non-ESS and ESS group of 17.5 (range of 3–68) and 44 (range of 10–73), respectively. Conclusions: ESS represents the best option to improve clinical QoL of CF patients who do not response to conventional medical therapy.